A revision of genus Vatica L. (Dipterocarpaceae) in Borneo, III: Stigma variant of some selected Vatica species from Sabah and Sarawak - Meekiong, Kalu; Nizam, M.S.; Latiff, A. (Gupta Publications, 2023)
The family Dipterocarpaceae is an important tropical forest tree with 15 genera and over 600 species worldwide. The genus Vatica was first described by Linnaeus in 1773 and was the third-largest genus in the family with approximately 80 species in the world. About 71 species are distributed in Malesia and 44 of them are recorded in Borneo. Those make Borneo island the best representative and considered an epicentre of the species. Vatica is the most difficult genus in Dipterocarpaceae to study as it has excessive variation in-term of habit, habitat, morphological and anatomical features. Informally the genus has been divided into three sections; Sunaptea, Vatica and Pachynocarpus based on the calyx morphology. An inclusive study on the stigma was piloted on 13 selected Vatica taxa to examine disparities in shapes that may be useful in the classification and identification of species. Eight types of stigma shapes were observed on the 13 selected Vatica species, viz. cordate, hexagonal, ovoid, perigonal, semispherical, stars, quadrogonal and ovolanceolate. The tremendous stigma variants of the Vatica flowers resulted that the stigma types could be a good supportive characteristic for species identification. Keywords: Vatica, stigma type, dipterocarpaceae, dipterocarps